2018
DOI: 10.1115/1.4038751
|View full text |Cite
|
Sign up to set email alerts
|

A Re-Engineered Software Interface and Workflow for the Open-Source SimVascular Cardiovascular Modeling Package

Abstract: Patient-specific simulation plays an important role in cardiovascular disease research, diagnosis, surgical planning and medical device design, as well as education in cardiovascular biomechanics. simvascular is an open-source software package encompassing an entire cardiovascular modeling and simulation pipeline from image segmentation, three-dimensional (3D) solid modeling, and mesh generation, to patient-specific simulation and analysis. SimVascular is widely used for cardiovascular basic science and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 77 publications
1
53
0
3
Order By: Relevance
“…Using a resistive model of an epicardial stenosis (0-80% diameter reduction) in series with the coronary microcirculation at maximal vasodilation, FFR was evaluated for changes in coronary microvascular resistance (0.1-0.6 mmHg.min/ml), aortic pressure (between 70 and 130 mmHg), and coronary outflow pressure (0-15 mmHg), and it was found that the sensitivity of FFR to these hemodynamic changes was highest for stenoses of intermediate severity (23). Recent studies employ either a patient-specific lumped-parameter model of the coronary circulation (9) or applied the SimVascular Cardiovascular Modeling Package (24). Meta-analysis of FFR vs. quantitative coronary angiography and non-invasive imaging for evaluations of myocardial ischemia resulted in relatively poor concordance among outcomes (22).…”
Section: Discussionmentioning
confidence: 99%
“…Using a resistive model of an epicardial stenosis (0-80% diameter reduction) in series with the coronary microcirculation at maximal vasodilation, FFR was evaluated for changes in coronary microvascular resistance (0.1-0.6 mmHg.min/ml), aortic pressure (between 70 and 130 mmHg), and coronary outflow pressure (0-15 mmHg), and it was found that the sensitivity of FFR to these hemodynamic changes was highest for stenoses of intermediate severity (23). Recent studies employ either a patient-specific lumped-parameter model of the coronary circulation (9) or applied the SimVascular Cardiovascular Modeling Package (24). Meta-analysis of FFR vs. quantitative coronary angiography and non-invasive imaging for evaluations of myocardial ischemia resulted in relatively poor concordance among outcomes (22).…”
Section: Discussionmentioning
confidence: 99%
“…A resistance boundary condition is used at the outlet equal to R = 1600 g/cm 4 /s, which produces a mean pressure of approximately ∆P = 100 mmHg, typical of the systemic circulation of a healthy subject. Simulations are performed with rigid and deformable walls (see Figure 1), using 1,002,436 tetrahedral elements for the fluid domain and 192,668 tetrahedral elements for the wall, generated in SimVascular with the TetGen mesh generator plugin [38,19]. We measure the wall clock time on the XSEDE Comet cluster for simulations consisting of 10 time steps of 1 millisecond each, using 38 and 48 cores for rigid and deformable simulations, respectively.…”
Section: Linear Solver Performance On Pipe Flow Benchmarkmentioning
confidence: 99%
“…ALE is a realistic and computationally intensive approach to solve the Navier-Stokes equations, the equations for solid mechanics, and the mesh motion equations in a monolithic fashion. We take advantage of recent developments in the SimVascular open-source software package, 37 namely the svFSI flow solver which provides an implementation of ALE FSI. The aim of the study is 3-fold.…”
Section: Introductionmentioning
confidence: 99%